The Influence of Price, Location, Promotion, and Service on Product Purchase Decision Making During The Covid-19 Pandemic (Case Study on Small and Medium Enterprises (UKM) of Kampung Sejahtera Mandiri Teras Pancasila Tangerang City, Banten) - Gregorius Widiyanto; Pujiarti Pujiarti (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study was to determine how much influence the independent variables (price, location, promotion, and service) had on the dependent variable (product purchasing decisions), either partially or simultaneously. This research was conducted at the Small and Medium Enterprises (MSMEs) of Kampung Sejahtera Mandiri, Teras Pancasila, Tangerang City, Banten. The sample used was taken by simple random sampling method as many as 100 consumers. Collecting data through field studies by distributing questionnaires to 100 consumers, as well as observations and interviews with SMEs in Kampung Sejahtera Mandiri Teras Pancasila, Tangerang City, Banten. Statistical data analysis used validity, reliability, normality, heteroscedasticity, multicollinearity, coefficient of determination, t test (partial test), and F test (simultaneous test), with the SPSS 25 statistical tool. significant on the dependent variable with the results obtained that the value of tcount price is 2,602 > ttable 1.65 and probability 0.0011 < 0.05, t-count value for location is 2.111 > ttable 1.65 and probability 0.0037 < 0.05, t-count promotion value is 6.101 > ttable 1.65 and probability of 0.0000 < 0.05, and the value of t count service is 6.648 > t table 1.65 and probability 0.000 < 0.05. The F test shows that the independent variable simultaneously has a positive and significant effect on the dependent variable with the results obtained that the Fcount value is 128.419 > Ftable 3.87 and the probability value is 0.000 <0.05. The value of the coefficient of determination (R2) is 56.3%, meaning that the independent variables (price, location, promotion, and service) have a simultaneous influence of 56.3% on the dependent variable (product purchasing decisions), and the remaining 100% - 56.3% = 43.7% influenced by other factors.